Gambaran Sarana Proteksi Aktif Kebakaran Dan Kepatuhan Konsumen Pada Tanda Dan Rambu Peringatan Di SPBU Sebagai Upaya Pencegahan Kebakaran - Lestari, Ayu Mega; Indrayani, Reny; Akbar, Kurnia Ardiansyah (Jurnal Ilmu Kesehatan Masyarakat, 2019)
One of the workplaces that often occurs in fires is a Petrol Station. As an effort to prevent fire with the availability of fire protection facilities available at gas stations. The purpose of this study is to describe the means of active fire protection and consumer compliance with warning signs and signs contained by gas stations as an effort to prevent fires in the Petrol Station Regency of Bondowoso. This research uses a descriptive quantitative research that illustrates the level of compliance with SPBU Safety Man Module regulations, SPBU Standard Operating Procedures and Management, K3LL Guidelines, Public Works Minister Regulation No: 26/PRT/M /2008 and SNI based on actual conditions. The sample in this study were 7 Petrol Station in Bondowoso Regency and 100 individuals related to consumer compliance. Data collection was carried out by interview, observation and documentation study. The average result of the suitability level of active protection facilities is 24.6% with the APAR criteria where the suitability level reaches 61.9% and the absorbance of sand reaches 85.71%. For fire detectors, fire alarms, fire hydrants and hose reels have not been implemented. While the level of consumer compliance is 95.83%. The results showed that active fire protection facilities at gas stations were not in accordance with laws and regulations, while consumer compliance was in the good category.